Specific amino acid substitutions in β strand S2 of FtsZ cause spiraling septation and impair assembly cooperativity in Streptomyces spp. Issue 1 (17th May 2019) - Sen, Beer Chakra; Wasserstrom, Sebastian; Findlay, Kim; Söderholm, Niklas; Sandblad, Linda; von Wachenfeldt, Claes; Flärdh, Klas
Summary: Bacterial cell division is orchestrated by the Z ring, which is formed by single‐stranded treadmilling protofilaments of FtsZ. In Streptomyces, during sporulation, multiple Z rings are assembled and lead to formation of septa that divide a filamentous hyphal cell into tens of prespore compartments. We describe here mutant alleles of ftsZ in Streptomyces coelicolor and Streptomyces venezuelae that perturb cell division in such a way that constriction is initiated along irregular spiral‐shaped paths rather than as regular septa perpendicular to the cell length axis. This conspicuous phenotype is caused by amino acid substitutions F37I and F37R in β strand S2 of FtsZ. The F37I mutation leads, instead of regular Z rings, to formation of relatively stable spiral‐shaped FtsZ structures that are capable of initiating cell constriction. Further, we show that the F37 mutations affect the polymerization properties and impair the cooperativity of FtsZ assembly in vitro . The results suggest that specific residues in β strand S2 of FtsZ affect the conformational switch in FtsZ that underlies assembly cooperativity and enable treadmilling of protofilaments, and that these features are required for formation of regular Z rings. However, the data also indicate FtsZ‐directed cell constriction is not dependent on assembly cooperativity. Abstract : Mutations were identified in ftsZ that give rise to spiraling cell constrictions instead of the regularly spaced septa that normally convert hyphae to spores in Streptomyces spp. The mutations affect a conserved region of FtsZ (β strand S2 and α helix H1), cause FtsZ to assemble into helical structures in the cell, and abolish the cooperativity in polymerization assays in vitro . The data suggest that this region of FtsZ is critical for cooperative assembly and proper Z‐ring formation, probably by affecting treadmilling, and further indicate that these features are not required for cell constriction.